Protein extract of Detam 1 soybean contains β–conglycinin stimulating cholecystokinin signal transduction through activities of PKC, c-RAF and ERK 1/2 in Wistar rats - Melinah Hidayat (Biomedical Engineering, 2015)
UNCORRECTED PROOFFOR REVIEWERBEBIOMEDICAL ENGINEERINGjournal homepage: be.ub.ac.idProtein extract of Detam 1 soybean contains β–conglycinin stimulatingcholecystokinin signal transduction through activities of PKC, c-RAF and ERK1/2 in Wistar ratsMeilinah Hidayat1†, Ahmad Faried21Nutrition Department Faculty of Medicine, Maranatha Christian University Bandung2Research and Development Unit Faculty of Medicine, Padjadjaran University, BandungA R T I C L E I N F OArticle history:Received: February 2015Accepted: June 2015Available online:August 2015Keywords:β conglycininCholecystokininProtein Extract of Detam 1soybeanSignal transduction†Corresponding author:Nutrition DepartmentFaculty of Medicine,Maranatha ChristianUniversity BandungE-mail:mellahidayat@yahoo.comA B S T R A C T1. IntroductionThe prevalence of obesity is definitelyincreasing and is widely spread in all over theworld (1). This condition should be overcomebecause obesity can cause many side effects. Oneof options solution is to discover good nutritionsources that can reduce body weight. Soybean(Glycine Max L. Merr) is a good source ofprotein. It has two major protein fractions, β-conglycinin (7S) and glycinin (11S) (2). β -conglycinin’s function was known to suppressfood intake, decreasing appetite (3) reducing bodyweight and this effect may be due to stimulatinggastrointestinal hormones, cholecystokinin (CCK)release (4). CCK is a peptide hormone of thegastrointestinal system that can act as a shortterm food intake inhibitor, has beendemonstrated to reduce food intake in a doserelatedmanner in different species andexperimental designs (5, 6, 7, 8).Protein can stimulate CCK secretion in STC-1cells duodenum through signal transduction of GProtein Coupling Receptor (GPCR) mechanisms(9). There are many possibilities in the pathway,such as Protein Kinase C (PKC), DiAcyl Glycerol(DAG), Protein Kinase (PKA), c-Raf andExtracellular Signal-Related Kinase (ERK) orMitogen Activated Protein Kinase (MAPK) (9).However, the cellular mechanisms by which theβ-conglycinin induces CCK secretion remain to beclarified.There hasn’t been many studies aboutIndonesian soybean variety in the relation to CCKObjective: to determine which kind of soybean extract contains the highest β-conglycinin level, their effects tocholecystokinin (CCK) plasma level, and to signal transduction pathway in duodenum of Wistar rats.Methods: β-conglycinin were analysed in vitro using sodium dodecyl sulphate polyacrylamide gelelectrophoresis (SDS PAGE) and coomassie brilliant blue (CBB) staining. The CCK plasma level were measuredin vivo in 24 male Wistar rats by ELISA method, using t-test paired and the activity of PKCμ, PKA, c-Raf and ERKin CCK signal transduction pathway in vivo by Western blot method and Scion image densitometry (DU)analysed using ANOVA.Result: Protein extract of Detam 1 soybean (PEDS) contains the highest amount of β-conglycinin level. Therewas no significant diffrerence of CCK plasma level between pre and post treatment (p> 0.05) although there wereincreasing level in all treatment. The duodenum of Wistar rats which were given PEDS showed significantdifference with negative control in signal transduction activities of PKCμ, c-Raf & ERK 1/2 pathway (p<0.001).Conclusion: PEDS contains the highest β-conglycinin level, effects to CCK plasma level, and to CCK signaltransduction pathway through activities of PKCμ, c-Raf and ERK 1/2 in enteroendocrine cells in duodenumWistar rats